The Legal Nature of Investment Contracts - الموسوي, علي فوزي; كاظم, حيدر محمود (Journal of Legal Sciences, 2021)
The investment contract that has a foreign element is considered amongst the contracts that have their legal and international economical weight, for what it represents in all countries’ economies, and achieving progress in many fields that investment has its effects on their growth and establishment as its at the centre of everyone’s attention. As well as that the variety in opinions and the presence of differences in the contents of these contracts, and the confusion between them and other international contracts, and the considerable interest jurists have in them have all led to not having a legal definition for them, as most definitions the describe them are more economical than they are legal, and the reason for that is that law protects them and provides the economical relationships and provides safety and stability and works on developing them, also, determining their legal nature has its considerable importance, and determining its laws changes according to the awareness of the legal nature, and then taking it back to what is being worked with in these international private relationships, so if the contract has a administrative nature it lies under the control of the administrative law, thus, what controls the relationship are the rules of the general law, and if the relationship has commercial and civil qualities, then it lies under the control of civil laws and is controlled by the private law.